2006
DOI: 10.1109/tpami.2006.217
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Pedestrian Classification

Abstract: Detecting people in images is key for several important application domains in computer vision. This paper presents an in-depth experimental study on pedestrian classification; multiple feature-classifier combinations are examined with respect to their ROC performance and efficiency. We investigate global versus local and adaptive versus nonadaptive features, as exemplified by PCA coefficients, Haar wavelets, and local receptive fields (LRFs). In terms of classifiers, we consider the popular Support Vector Mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
354
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 506 publications
(369 citation statements)
references
References 13 publications
4
354
0
5
Order By: Relevance
“…In this sense, the choice of the feature extractors, histogram of oriented gradients (HOG) and local receptive fields (LRF), was motivated by the studies found in , Munder and Gavrila (2006) and Szarvas et al (2006). presented an experimental analysis demonstrating that HOG features outperforms PCA-SIFT, Haar wavelets and shape contexts in a complex data set.…”
Section: Example Of Detection By Classifier Ensemblementioning
confidence: 99%
“…In this sense, the choice of the feature extractors, histogram of oriented gradients (HOG) and local receptive fields (LRF), was motivated by the studies found in , Munder and Gavrila (2006) and Szarvas et al (2006). presented an experimental analysis demonstrating that HOG features outperforms PCA-SIFT, Haar wavelets and shape contexts in a complex data set.…”
Section: Example Of Detection By Classifier Ensemblementioning
confidence: 99%
“…To illustrate that SCA captures the variability in the data in a substantially different way than a mixture of PIMs (MPIM, of the same complexity, we considered the Daimler dataset (Munder and Gavrila 2006). The full dataset is composed by 10200 gray levels images at a resolution of 18 × 36 pixels.…”
Section: A Comparison Between Sca's Components and The Centers Of A Mmentioning
confidence: 99%
“…[1]- [4], [7], [13], [17]- [19] Local features are extracted from training dataset and a classifier can be obtained by using some training method, such as support vector machine [20], or some boosting methods [21]. HOG feature in [1] is one of the most efficient features recently.…”
Section: Related Workmentioning
confidence: 99%
“…Haar-like feature is proposed in [13], integral image is calculated for acceleration and cascade structure is used, which is widely used in many object detection methods. Local Receptive Fields (LRF) feature [17] and Haar wavelets feature [19] are also used in human detection. Learning based method is efficient for human detection.…”
Section: Related Workmentioning
confidence: 99%